Handbook of numerical heat transfer - Minkowycz, W.J (Wiley, 1988)
Presents a comprehensive, accessible and readily usable reference to the necessary formulations, numerical schemes, and innovative solution techniques for solving problems of heat and mass transfer and related fluid flows. Grouped by major sets of methods and functions, the text describes new or improved, as well as standard, procedures. This collection of contributions from leading figures in the field covers parabolic systems, hyperbolic systems, integral and integro-differential systems, Monte Carlo and perturbation methods, inverse problems and more.